2008
DOI: 10.1007/s10803-008-0550-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Face Familiarity in Eye Tracking of Faces by Individuals with Autism Spectrum Disorders

Abstract: It has been shown that individuals with autism spectrum disorders (ASD) demonstrate normal activation in the fusiform gyrus when viewing familiar, but not unfamiliar faces. The current study utilized eye tracking to investigate patterns of attention underlying familiar versus unfamiliar face processing in ASD. Eye movements of 18 typically developing participants and 17 individuals with ASD were recorded while passively viewing three face categories: unfamiliar non-repeating faces, a repeating highly familiar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 57 publications
(62 reference statements)
7
77
0
Order By: Relevance
“…This is because an atypical pattern of mutual gaze behaviour, or eye contact, is among the most distinguishable manifestation of the qualitative impairment in social interaction in ASD. Since Kanner's first report (Kanner, 1943(Kanner, , 1944, such atypical pattern of eye contact has been reported and discussed in many clinical and experimental settings, including recent studies using eye-tracking methods ( Figure 1, Boraston et al, 2008;Dalton et al, 2005;Pelphrey et al, 2002;Spezio et al, 2007c;Sterling et al, 2008, but see also Dapretto et al, 2006;Rutherford & Towns, 2008;van der Geest et al, 2002). Based on this clinical significance, eye contact is currently included in standardised diagnostic criteria such as DSM-IV-TR (American Psychiatric Association, 2000) and ICD-10 (World Health Organization, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…This is because an atypical pattern of mutual gaze behaviour, or eye contact, is among the most distinguishable manifestation of the qualitative impairment in social interaction in ASD. Since Kanner's first report (Kanner, 1943(Kanner, , 1944, such atypical pattern of eye contact has been reported and discussed in many clinical and experimental settings, including recent studies using eye-tracking methods ( Figure 1, Boraston et al, 2008;Dalton et al, 2005;Pelphrey et al, 2002;Spezio et al, 2007c;Sterling et al, 2008, but see also Dapretto et al, 2006;Rutherford & Towns, 2008;van der Geest et al, 2002). Based on this clinical significance, eye contact is currently included in standardised diagnostic criteria such as DSM-IV-TR (American Psychiatric Association, 2000) and ICD-10 (World Health Organization, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…These claims are based on the large number of studies documenting reduced attention to faces (Hutt and Ounsted 1966;Trepagnier et al 2002;Riby and Hancock 2008;Sasson et al 2007;Bal et al 2010;Baranek 1999;Chawarska and Shic 2009;Osterling and Dawson 1994;Osterling et al 2002;Hernandez et al 2009) and/or atypical eye fixation in autism (as initially detailed in Kanner's first descriptions of autism, Kanner 1943Kanner , 1944; see also Joseph and Tanaka 2003;Riby and Hancock 2008;Boraston et al 2008;Sterling et al 2008;Jones et al 2008; for a review see Senju and Johnson 2009a). Klin et al (2002) assessed fixation patterns while participants observed emotional movie clips containing social interaction.…”
mentioning
confidence: 99%
“…Familiarity of interlocutor will influence the amount of GA (Argyle & Dean, 1965;Rubin, 1970;and cf Sterling et al 2010) for typically developing children. We predict no difference associated with familiarity in children with ASD (Sterling et al, 2010);…”
Section: Ws and Asd And The Use Of Gaze Aversionmentioning
confidence: 64%
“…We know in typical adults and children that amount of eye contact is in part determined by the closeness of the social relationship (and familiarity is part of this) with, for example, more looking between close friends than strangers (Argyle & Dean, 1965;Rubin). In contrast Sterling, Dawson, Webb, Murias, Munson, Panagiotides and Aylward (2010) report that typically developing adults actually spent less time fixating on familiar faces than unfamiliar faces. One interpretation of this is that participants had to spend more time processing the unfamiliar information in the unfamiliar faces.…”
Section: Ws and Asd And The Use Of Gaze Aversionmentioning
confidence: 89%
See 1 more Smart Citation